Estimasi Parameter Model Suku Bunga Vasicek menggunakan Metode Jackknife pada Bank Indonesia - Khairunnisa, Michi; Arnellis, Arnellis (UNIVERSITAS NEGERI PADANG, 2024)
Stochastic interest is exemplified by the Vasicek Interest Rate Model. Interest rates change from time to time. This study is a type of applied research in which the Jackknife Method to gauge the characteristics of the parameters of the Vasicek Interest Rate Model. The Jackknife method of parameter estimation involves resampling, which is done by taking out one observation from the data and repeating the process as often as necessary. The Jackknife technique is used to get estimates from observation with a small sample size. The goal of this study is to understand the Jackknife Method’s estimate findings for the Vasicek Model parameters. The Vasicek Model parameter estimate process involves numerous steps, including establishing the recursive solution, changing the equation into a regression form, then transformation to the matrix and estimation to the parameter using the Jackknife technique. By following the step, it is possible to determine that the Vasicek interest rate model parameters is 0.20424, 0.38909 , as well as 0.28083.